Fungal Infection: A Recent Concern for Physician (Bangladesh Journal of Medicine, 2022)
Fungal diseases are an important determinant of survival in immunocompromised patients and in patients with chronic illnesses. Fungal infections in Bangladesh are diverse, and many studies have documented their frequency. A better understanding of the epidemiology, clinical features, and diagnostic method of fungal infection is integral to improving outcomes. In this review, we discuss the emergence of fungal infection along with the clinical pictures, diagnosis, and treatment of different fungal infections that are prevalent in our country. It is hoped that this article will create greater awareness of the burden of fungal infections on public health and promote effective diagnosis and therapy.Bangladesh J Medicine 2022; 33: 235-240